2018
DOI: 10.1002/pon.4863
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes in cancer‐bereaved children and adolescents: A systematic review

Abstract: Results indicate a high level of adjustment in cancer-bereaved children and adolescents. A modifiable risk factor for adverse psychosocial consequences is poor communication. Prospective designs, representative samples, and validated instruments, eg, for prolonged grief, are suggested for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 72 publications
(382 reference statements)
0
19
0
Order By: Relevance
“…If the index of discriminating power, which is related to variance and score distribution gets higher than 90%, the scale will be good. The obtained coefficients in the CBCL form were at the highest level (17).…”
Section: Child Behavior Checklist (Cbcl)mentioning
confidence: 88%
“…If the index of discriminating power, which is related to variance and score distribution gets higher than 90%, the scale will be good. The obtained coefficients in the CBCL form were at the highest level (17).…”
Section: Child Behavior Checklist (Cbcl)mentioning
confidence: 88%
“…Most studies in the field of grief and bereavement have been conducted with children/adolescents or adults [39][40][41], and little is known of how university students have experienced grief and personal growth. This study aimed to address this gap and intended to explore the detrimental effects of loss amongst university students, as well as how students may have experienced personal growth after the loss during this time in life.…”
Section: Aimsmentioning
confidence: 99%
“…Regarding cancer bereavement specifically, a systematic review of the child and AYA sibling and offspring literature in this area was recently conducted by Hoffmann, Kaiser, and Kersting [11]. They found that adolescents in particular tend to have a greater vulnerability to behavioural problems and depression/anxiety symptoms in comparison to children and young adults.…”
Section: Ayas and Cancer Bereavementmentioning
confidence: 99%
“…They found that adolescents in particular tend to have a greater vulnerability to behavioural problems and depression/anxiety symptoms in comparison to children and young adults. This is potentially due to adolescents having a greater depth of understanding of the consequences and complexities of death and loss than children [11], but having poorer social and emotional skills to cope with the loss than young adults [12]. Furthermore, Hoffmann et al [11] reported unresolved grief in approximately 50% of cancer bereaved AYAs two to nine years after the death, and heightened risk of self-injury in young adults who had a parent die of cancer during their teenage years compared with their nonbereaved peers.…”
Section: Ayas and Cancer Bereavementmentioning
confidence: 99%